Delayed Anticoagulation-Related Intracranial Haemorrhage after Minor Head Injury. (4th December 2013) - Beynon, Christopher; Orakcioglu, Berk; Winkler, Harald; Geis, Nicolas A.; Unterberg, Andreas W.; Sakowitz, Oliver W.
Abstract : Treatment with anticoagulants and antiplatelet agents are well-known risk factors for an unfavourable outcome after traumatic brain injury (TBI). Guidelines for decision making in patients who sustained mild head injury do not apply to anticoagulated patients and therefore, in these cases diagnostic and therapeutic procedures have to be tailored patient-specific. A 69-year-old patient was referred to our hospital after sustaining mild head injury. Due to anticoagulation therapy, a cranial computed tomography was carried out and was without pathologic findings. After negative workup for TBI, the patient was admitted to the ward solely because of intermittent cardiac arrhythmia. The next day, the patient developed a hemiparesis and repeated brain imaging showed a large posttraumatic intracranial haematoma which had to be evacuated surgically. In the further clinical course, the patient recovered completely and a cardiac pacemaker was implanted. Emergency physicians have to be highly alert with anticoagulated patients after head injury, even if the trauma was mild and initial diagnostic procedures demonstrate no acute pathology. Delayed traumatic intracranial haemorrhage may have fatal consequences for patients and while the threshold for admission to a hospital ward should be low, adequate observation at home has to be ensured if patients are discharged.